2006
DOI: 10.2113/gsecongeo.101.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Geology, Geochronology, and Hf and Pb Isotope Data of the Raul-Condestable Iron Oxide-Copper-Gold Deposit, Central Coast of Peru

Abstract: Raúl-Condestable is a >32 million metric ton (Mt) iron oxide-copper-gold (IOCG) deposit located on the Peruvian coast, 90 km south of Lima. The ore occurs as veins, replacement "mantos," and disseminations consisting of a chalcopyrite-pyrite-pyrrhotite-magnetite-amphibole mineral association. The geology of the studied area comprises a series of superposed volcanic edifices of Late Jurassic to Early Cretaceous age, which are part of a larger volcanic island to continental arc system. Particularly good exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 72 publications
2
11
0
1
Order By: Relevance
“…However, the lack of inherited zircons in the dacite suggests that crustal contamination only played a minor role in the petrogenesis (De Haller et al, 2006).…”
Section: Tugutublak Formation Tuffaceous Dacitic Lavamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of inherited zircons in the dacite suggests that crustal contamination only played a minor role in the petrogenesis (De Haller et al, 2006).…”
Section: Tugutublak Formation Tuffaceous Dacitic Lavamentioning
confidence: 99%
“…14c-d), with a tectonic regime unambiguously dominated by back (intra)-arc basin-arc transition. These Central Andean batholiths are widely accepted to be dominantly generated by the remelting of isotopically juvenile crust (e.g., back-arc basin basaltic rocks) and mixing with minor mantle components during basin inversion (Atherton, 1990;Polliand et al, 2005;De Haller et al, 2006;Mišković and Schaltegger, 2009;Boekhout et al, 2012;Cochrane et al, 2014).…”
Section: Implications For Tectonic Settingmentioning
confidence: 99%
“…A major part of the plutonic rocks from central and northern Peru (between 14 and 5°S) were emplaced between 90 and 65 Ma, with some intrusions around 117 and 100 Ma (De Haller et al, 2006;Mukasa, 1986a). In Chile, distinct episodes of pluton emplacement have also been described between 18°S and 56°S.…”
Section: Gap In the Magmatic Activity And Arc Migrationmentioning
confidence: 99%
“…A direct connection between IOCG ore-forming processes and tholeiitic to calc-alkaline, subduction-related magmatism has been identified (Vila et al, 1996;Marschik and Fontboté, 2001;Rhodes and Oreskes, 1999;Sillitoe, 2003;de Haller et al, 2006). Although field evidence and more recent data from fluid inclusions and stable isotopes have confirmed that the intervention of nonmagmatic fluids, e.g., seawater or evaporite-derived basinal brines, may play an important role in the generation of Cu (-Au) mineralization (Ripley and Ohmoto, 1977;Ullrich and Clark, 1999;Ullrich et al, 2001;de Haller et al, 2002;Benavides et al, 2007;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%